An Endless Struggle of Fighting Discrimination in the Name of Human Rights Protection - Hernadi Affandi; Tarsisius Murwadji (Faculty of Law, Universitas Padjadjaran, 2020)
The Incident of George Floyd’s death reminds people of the peril of discrimination that still exists within the American society. The incident has triggered worldwide reactions from people who feel sympathy for the victim and reject racism. To eliminate racial discrimination, every modern society needs to remove any negative paradigm towards intergroup relation. In the context of the United States, the American Government has the responsibility to protect the rights of citizens from any forms of discrimination. That includes racial discrimination. In addition, people have to be reminiscent of the danger of racial discrimination in the modern era. The danger has the ability to disturb human rights protection. This study revealed history, criteria, and impacts of discrimination within the scope of human rights protection.Memerangi Diskriminasi dalam Perlindungan Hak Asasi Manusia: Perjuangan Tiada Akhir Abstrak Insiden George Floyd seakan mengingatkan kembali bahaya diskriminasi yang masih ada di masyarakat AS. Kejadian itu memunculkan reaksi dari orang-orang yang turut bersimpati dan menolak rasialisme dari seluruh belahan dunia. Masyarakat modern semestinya sudah mengubah pandangannya yang negatif terhadap kelompok lain, sehingga tidak terjadi diskriminasi rasial. Oleh karena itu, pemerintah AS memiliki tanggung jawab untuk melindungi hak warga negaranya dari segala bentuk diskriminasi termasuk diskriminasi rasial. Di samping itu, masyarakat perlu diingatkan kembali tentang bahaya diskriminasi rasial di era modern yang dapat mengganggu perlindungan hak asasi manusia. Tulisan ini akan menyoroti tentang sejarah, tolak-ukur, dan akibat diskriminasi terhadap perlindungan hak asasi manusia.Kata kunci: afro-amerika, diskriminasi-rasial, hak asasi manusia.DOI: https://doi.org/10.22304/pjih.v7n2.a4